2014
DOI: 10.1177/2151458514520700
|View full text |Cite
|
Sign up to set email alerts
|

Total Hip Arthroplasty for Hip Fractures

Abstract: Introduction: This study aimed to determine the dislocation and reoperation rate, functional outcomes, and the survival rate of the unique subset of very old but lucid and independent patients with hip fractures following a total hip arthroplasty (THA) and geriatric team-coordinated perioperative care. Method: Between 2000 and 2006, previously independent ambulatory patients 80 years old presenting with an intracapsular hip fracture were given THAs under the care of an integrated orthopedic surgerygeriatric se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Although none of the patients in this study suffered falls during the monitoring, the related literature highlights the need to establish evaluation and fall prevention programs after arthroplasty surgeries. This policy becomes imperative due to the risks presented by patients undergoing THA, who mostly have functional limitations and advanced age ( 19 ) . In the study sample, the NOC scores showed that the patients presented from moderate to frequent fall prevention behavior, demonstrated throughout the evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Although none of the patients in this study suffered falls during the monitoring, the related literature highlights the need to establish evaluation and fall prevention programs after arthroplasty surgeries. This policy becomes imperative due to the risks presented by patients undergoing THA, who mostly have functional limitations and advanced age ( 19 ) . In the study sample, the NOC scores showed that the patients presented from moderate to frequent fall prevention behavior, demonstrated throughout the evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…The recently published 5-year follow-up of functional outcomes in the oldest independent old and very old patients (>80 years old) with previously good functional status has demonstrated that with appropriate surgical and geriatric care, they have few hip dislocations and reoperations, survive postfracture at least as long as their noninjured contemporaries, and continue to function and ambulate as they did prior to their injury. 17 It is noteworthy that when the fracture fixation is followed by acute THA, the perfect reduction of fracture is not required. The resected femoral head may be used for the autograft of bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…Total hip arthroplasty (THA) is a saving procedure used to relieve pain and functional disability associated with many hip problems, most commonly, primary hip osteoarthritis, posttraumatic arthritis, and avascular necrosis in sickle cell disease patients [1][2][3][4][5][6]. Sickle cell disease is endemic in Saudi Arabia due to the high percentage (57.7%) of consanguineous marriages, rising to more than 80% in some rural areas [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main complications of THA for sickle cell disease (SCD) patients is periprosthetic hip fracture [1][2][3][4][5][6]. The incidence of fracture is affected by gender, age, race, BMI, implant fixation type, proximal femoral morphology, sickle cell genotype, and hemoglobin (Hb) level [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation